Pour une géographie processuelle : géo-anthroposystème et logique ternaire - Henri Reymond (Unité Mixte de Recherche 8504 Géographie-cités, 2016)
What does the term “process” mean for a geographer, conceptually and operationally? Do processual structures exists, structures that engender, unfold and delimit a process? This paper offers an answer based on the contradictory antagonistic ternary logic of S. Lupasco and a personal interpretation of man’s technical evolution.